LAWAN HIPERTENSI DENGAN CARA POLA HIDUP SEHAT DAN TERAPI MEDITASI DI DUSUN VI DESA PATUMBAK 1 KECAMATAN PATUMBAK - Nurul Aini Siagian; Septa Dwi Insani; Yunita Syahputri Damanik; Eka Sri Wahyuni; Fitriani Fitriani; Arnida Chaniago (INSTITUT KESEHATAN DELI HUSADA, 2026)
Hypertension is a chronic cardiovascular complication driven by a complex interaction of physical and psychological stressors. In Dusun VI, Patumbak 1 Village, the hypertension prevalence hit 36.1% due to high daily stress levels and a complete lack of non-pharmacological relaxation management within the community. Objective: To analyze the effectiveness and contribution of implementing meditation therapy and healthy lifestyle modifications in controlling blood pressure among hypertensive patients in Dusun VI, Patumbak 1 Village, Patumbak District in 2026. Methods: This study utilized a descriptive quantitative approach with a cross-sectional design. A sample of 166 households was selected via purposive sampling from a total population of 284 households using the Slovin formula. Primary data collection relied on structured questionnaires, analyzed through the CARL matrix and Fishbone Diagram. The entire methodology is fully structured in single-flowing narrative paragraphs. Results: Situation analysis highlighted hypertension as the top health priority with a CARL score of 199. The underlying root cause was dominated by unmanaged emotional distress and the absence of mind-relaxation habits. Interventions heavily focused on guided meditation training and healthy lifestyle changes. Post-activity evaluations showed an 85% surge in community knowledge and motor skills regarding self-meditation practices for stress reduction. Conclusion: Meditation therapy is highly effective as a complementary non-pharmacological approach to lower blood pressure by inducing a relaxation response that dampens sympathetic nervous overactivity and improves emotional stability.